Early Catheter Ablation Versus Initial Medical Therapy for Ventricular Tachycardia Storm. (18th November 2022) - Huang, Kaimin; Bennett, Richard G.; Campbell, Timothy; Lee, Vickie; Turnbull, Samual; Chik, William W.B.; El-Sokkari, Ihab; Hallani, Hisham; Dieleman, Jan; Kruit, Natalie; Eslick, Adam; Priestley, Mark; et al.
Abstract : Background: Ventricular tachycardia (VT) storm is associated with significantly increased morbidity, mortality, and exponential healthcare utilization. Although catheter ablation (CA) may be curative, there are limited data directly comparing outcomes of early CA with initial medical therapy. Methods: We compared outcomes of patients presenting with VT storm treated with initial CA versus those treated with initial medical therapy during their first storm presentation in an observational study. Retrospective data from the host institution from January 2014 to April 2020 of 129 patients with their first VT storm presentation were analyzed (58 underwent initial CA, 71 underwent treatment with initial medical therapy). Outcomes were compared in follow-up. Results: Median time to initial CA was 6 days. Over a median follow-up of 702 days, patients who underwent initial CA compared with those treated with initial medical therapy had significantly less: (i) VA recurrence (43% versus 92%; P =0.002); (ii) VT storm recurrence (28% versus 73%; P <0.001); (iii) composite end point of death, heart transplant, VT storm recurrence, and VT-related hospitalization (47% versus 89%; P =0.002); (iv) iatrogenic complications (at 12 months: 17% versus 45%; P <0.001); (v) cardiovascular-related hospitalizations (50% versus 89%; P =0.01); (vi) total number of hospitalizations (median 1 versus 4; P <0.001); and (vi) cumulative days in hospital (median 0.5 versus 18; P <0.001). There were no intraprocedural deaths in patients treated with early CA. Conclusion: In an observational setting in which patients presenting with storm, early CA appears superior to initial medical therapy in terms of VT recurrence, storm recurrence, iatrogenic complications, cardiovascular hospitalizations, and cumulative days in hospital in follow-up.